Nano Online 2016
DOI: 10.1515/nano.11671_2015.298
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic Acid Fullerene (C60) Derivatives Attenuated Neuroinflammatory Responses by Modulating Mitochondrial Dynamics

Abstract: Fullerene (C 60 ) derivatives, a unique class of compounds with potent antioxidant properties, have been reported to exert a wide variety of biological activities including neuroprotective properties. Mitochondrial dynamics are an important constituent of cellular quality control and function, and an imbalance of the dynamics eventually leads to mitochondria disruption and cell dysfunctions. This study aimed to assess the effects of carboxylic acid C 60 derivatives (C 60 -COOH) on mitochondrial dynamics and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…NRF2 mediates a set of adaptive responses to intrinsic and extrinsic cellular stresses [ 10 ]. Fullerene derivative C 60 (C(COOH) 2 ) 3 (C 60 -COOH) was investigated previously and it was demonstrated that C 60 -COOH pretreatment attenuated the lipopolysaccharide-mediated activation of nuclear factor- (NF-) κ B and mitogen-activated protein kinase (MAPK) signaling, as well as the production of proinflammatory mediators [ 11 ]. Nuclear factor- κ B is an essential transcription factor, which controls the expression of genes involved in the immune and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…NRF2 mediates a set of adaptive responses to intrinsic and extrinsic cellular stresses [ 10 ]. Fullerene derivative C 60 (C(COOH) 2 ) 3 (C 60 -COOH) was investigated previously and it was demonstrated that C 60 -COOH pretreatment attenuated the lipopolysaccharide-mediated activation of nuclear factor- (NF-) κ B and mitogen-activated protein kinase (MAPK) signaling, as well as the production of proinflammatory mediators [ 11 ]. Nuclear factor- κ B is an essential transcription factor, which controls the expression of genes involved in the immune and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%